Different Preparations of Cadaveric Costal Cartilage Compared to Autologous Rib Cartilage in Rhinoplasty: A Systematic Review and Meta-Analysis - Ahmed Wael Moftah; Ahmed Samy Gad; Mouhammed Sleiay; Nourhan Eid Abdelaziz (Facial Plastic Surgery & Aesthetic Medicine, 2026)
Background: The adoption of homologous costal cartilage (HCC) in rhinoplasty is hindered by conflicting reports on resorption and warping. Current literature often conflates fresh-frozen and irradiated grafts, obscuring distinct biological profiles. The objective of this systematic review and meta-analysis was to evaluate the clinical and biomechanical outcomes of different preparations of cadaveric costal cartilage compared to autologous rib cartilage in rhinoplasty. Methods: A systematic review was conducted per PRISMA 2020 guidelines (PROSPERO ID: CRD42025603758). Studies comparing homologous grafts versus autologous costal cartilage were stratified into fresh-frozen and irradiated subgroups. Primary outcomes compared these homologous subgroups explicitly against autologous cohorts regarding resorption, warping, and infection. Risk of bias was assessed using the Newcastle-Ottawa Scale and ROBINS-I tools. Results: Seven studies comprising 1,184 patients were included. Pooled analysis showed comparable infection rates between groups (risk ratios [RR] = 0.701; 95% CI: 0.284 to 1.731). Stratified subgroup analysis revealed that alcohol-preserved grafts demonstrated a significant reduction in warping risk (RR = 0.106; 95% CI: 0.012 to 0.934), while fresh-frozen and irradiated preparations showed comparable warping to autologous controls. Conversely, an elevated risk of resorption was driven exclusively by the irradiated subgroup (RR = 4.595; 95% CI: 1.279 to 16.503), whereas fresh-frozen (RR = 1.588; 95% CI: 0.489 to 5.164) and alcohol-preserved (RR = 1.479; 95% CI: 0.313 to 6.998) subgroups showed no significant difference. Operative time was significantly reduced in the homologous cohort (weighted mean differences = −66.56 min; 95% CI: −81.42 to −51.71). Conclusion: HCC represents a viable alternative to autologous rib in carefully selected cases, rather than a default substitute. While modern preservation methods offer promising short-term structural stability and eliminate donor-site morbidity, the decision of graft choice may be best made from individual patient and surgical factors, rather than the superiority of one source over the other.